(3GdCeKdI aj GdUQas - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3eOQSI JTd YeGQJ, eOjfI HQhSIs)
(3ChdgG (B:s
(3GdMeO ddg Ydi JUGQja fYeghHYO ajbhdGdLdGdEf eYQaI GdCeKdI GdJj gj ef fJGFL Yde GdUQa hGdGTJbGb hgj Chd eG jLH JYdegG Ydi GdeJYdejf HGdGJaGbaCQOJ Cf CYdegG dhdOjs
(3BNQgG (B:s
(3JeJ GdCeKdI ef NeSI hKdGKjf HGHG aef MaXgG aUhdG hCHhGHG abO HQY aj UjZ GdcdGe hced CSGSj GdCHfjI Ydi GdJeGe hLYdgG Gddg fGaYI ddWGdHjfs
(3aj Chdg fbhd aj GdfMh ef cJGH QhM GdTQhMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 301s
(3eYLe GdeDdajf(B: 2 / 82s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdUQas